High-Flow Nasal Cannula untuk Pengelolaan Acute Respiratory Distress Syndrome Akibat COVID-19 - Dimas Hadi Prayoga; Natalia Christin Tiara Revita; Devy Syanindita Roshida; Eska Distia Permatasari (FORIKES, 2024)
ARDS or Acute Respiratory Distress Syndrome defines a clinical condition of severe lung disease associated with pneumonia, sepsis and trauma which can be caused by SARS-Cov-2 or COVID-19. COVID-19-induced ARDS has a high mortality rate. The choice of mechanical ventilation is very important so that it can be used as appropriate treatment for ARDS caused by COVID-19, so it is necessary to review journals to obtain information related to preventing an increase in ARDS cases in COVID-19. A search strategy relevant to the study topic was carried out using the databases